A negative electrode material and its preparation method and application
By using a silicon-based negative electrode material with a double-layer core-shell structure in lithium-ion batteries, and using carbon base layer and metal phosphide shell structure, the problem of insufficient cycle stability and rate performance caused by changes in the volume of silicon-based materials is solved, and high Improved capacity density and cycle stability.
Patent Information
- Application Number
- CN202111572556.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-21
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-12-21
AI Technical Summary
The volume of the silicon-based anode material in lithium-ion batteries varies greatly during charging and discharging, resulting in insufficient cycle stability and rate performance, limiting the commercial application of batteries.
Using a negative electrode material with a double-layer core-shell structure, the silicon-based core is encased on a carbon base layer with a pore structure, and a metal phosphide shell is formed on the outer layer. The MOF material is synthesized through solvothermal reaction to generate a carbon base layer and a metal phosphide, forming a high-quality An anode material with capacity and high electronic conductivity.
It significantly improves the cycling stability and rate performance of the negative electrode material, and can maintain a capacity of 1287.18mAh/g after cycling at a current density of 4A/g for 800 weeks, with a capacity retention rate of ≥71.8%, and effectively suppresses damage caused by volume changes. , improves the battery life.
Smart Images

Figure CN114373909B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion battery (LIB) is a secondary battery with the advantages of large capacity, light weight and long life. The materials that can be used for the negative electrode of lithium-ion batteries include lithium metal (Li), silicon (Si), graphite, silicon carbon, tin selenide (SnSe x ), manganese tetraoxide (Mn3O4), rhenium disulfide (ReS2), etc. At present, graphite anode is the most mature anode in the commercial market, with excellent conductivity and good cycle stability, but its gram-specific capacity is low (372mAh g -1 ), is an obstacle to improving the energy density of lithium-ion batteries. In addition, although lithium metal anodes have advantages such as large theoretical capacity, low density, and low redox potential, the lithium dendrite problem they face is more serious than other types of anodes, and lithium dendrites may cause serious safety problems.
[0003] Silicon has a high theoretical capacity (4200mAh g -1 ), abundant resources, low price, etc., and are expected to replace the current graphite negative electrode for large-scale commercialization. However, before commercialization, the problem of large volume change (~300%) of silicon materials during charging and discharging must be overcome.
[0004] In order to solve the problem of silicon negative electrode, researchers have explored the following directions: first, nano-scaling silicon-based materials to alleviate the impact of volume expansion on battery performance; second, compounding silicon with other materials, such as silicon-carbon materials.
[0005] However, the above modification ideas have achieved limited results, and the cycle stability of the resulting silicon-based negative electrode still needs to be improved. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a negative electrode material, which can greatly improve the cycle stability of the silicon-based negative electrode through the design of structure and composition.
[0007] The present invention also provides a method for preparing the negative electrode material.
[0008] The present invention also proposes the application of the negative electrode material.
[0009] According to one aspect of the present invention, a negative electrode material is provided, comprising: a silicon-based core, a carbon-based layer wrapping the silicon-based core, and a metal phosphide wrapped on the surface of the carbon-based layer;
[0010] The carbon-based layer has a pore structure.
[0011] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved:
[0012] (1) The negative electrode material provided by the present invention has a double-layer core-shell structure, and the outermost shell is a metal phosphide. Through the conversion reaction, Li3P can be formed during the discharge process, thereby improving the storage capacity of Li+, that is, further improving the discharge capacity of the negative electrode material; at the same time, the metal phosphide also has excellent electrical conductivity, so the rate performance of the negative electrode material can be improved;
[0013] The middle layer is a carbon-based layer, which can improve the electronic conductivity of the negative electrode material and improve its rate performance;
[0014] The core is a silicon-based particle, which can take advantage of its unique high capacity density;
[0015] Therefore, the present invention can obtain a negative electrode material with high capacity and high electronic conductivity through structural design and synergistic effect between components.
[0016] (2) The present invention provides a carbon-based layer with a pore structure between the outermost metal phosphide and the silicon-based core, wherein the pore structure can increase the specific surface area of the negative electrode material and increase the capacity to accommodate Li + ability to provide a transmission channel and improve Li + The diffusion speed of the above negative electrode materials is further improved; on the other hand, the carbon-based layer with a pore structure has a certain deformation ability, which can accommodate the volume change of the silicon-based core during the charge and discharge process; in addition, the carbon in the carbon-based layer and the silicon in the silicon-based layer can form a strong Si-C chemical bond, promote the transfer of electrons, enhance the interaction between the silicon-based core and the carbon-based layer, and avoid the damage of the negative electrode material during the cycle;
[0017] The present invention uses a carbon-based layer and a metal phosphide double layer to wrap the silicon-based core. On the one hand, it can effectively suppress the damage caused by the volume expansion of the silicon-based core. On the other hand, even if part of the silicon-based material is damaged, it will not affect other negative electrode materials, let alone the normal operation of other components such as the electrolyte.
[0018] In summary, the present invention can significantly improve the cycle stability and rate performance of the negative electrode material through structural design.
[0019] (3) In the negative electrode material of the present invention, a synergistic effect occurs between the composition and the structure. Therefore, after the obtained negative electrode material is cycled for 800 cycles at a current density of 4 A / g, the reversible capacity is still as high as 1287.18 mAh / g, and the capacity retention rate is ≥71.8%, which has extremely high capacity density and cycle stability.
[0020] In some embodiments of the present invention, the metal phosphide includes at least one of iron phosphide, nickel phosphide, molybdenum phosphide and cobalt phosphide.
[0021] The iron phosphide, nickel phosphide, molybdenum phosphide and cobalt phosphide all have very excellent electronic conductivity.
[0022] In some embodiments of the present invention, the particle size of the negative electrode material is 1 to 3 μm.
[0023] In some embodiments of the present invention, the specific surface area of the negative electrode material is 300 to 400 m 2 / g.
[0024] In some embodiments of the present invention, the carbon-based layer has a thickness of 0.4-0.8 μm.
[0025] In some embodiments of the present invention, there is a gap between the carbon-based layer and the metal phosphide.
[0026] In some embodiments of the present invention, the silicon-based core comprises 200-500 nm nano-silicon.
[0027] The present invention adopts nano-scale silicon-based core to reduce Li + The diffusion distance can be shortened, the electronic conductivity can be improved, and the volume change during the charge and discharge process can be alleviated.
[0028] In some embodiments of the present invention, the carbon-based layer is doped with at least one of phosphorus and nitrogen.
[0029] Nitrogen and phosphorus can form Si-N bonds with the silicon-based core, enhancing the interaction between the carbon-based layer and the silicon-based core;
[0030] Nitrogen doping promotes the transfer of electrons, and phosphorus is doped into the silicon-carbon material as an electron donor. The combination of the two can adjust the electronic structure in the silicon-carbon material and thus improve its electronic conductivity.
[0031] According to another aspect of the present invention, a method for preparing the negative electrode material is provided, comprising the following steps:
[0032] S1. Solvothermal reaction of silicon-based particles, metal salts and ligands followed by solid-liquid separation to obtain silicon-based particles coated with MOF;
[0033] The ligand comprises a phosphorus-containing ligand;
[0034] S2. calcining the MOF-wrapped silicon-based particles in a protective atmosphere.
[0035] The reaction mechanism of the preparation method is as follows:
[0036] In step S1, a layer of phosphorus-containing MOF material is synthesized in situ on the surface of silicon-based particles by a solvothermal method;
[0037] In step S2, the solid obtained in step S1 is calcined, and a carbon-based layer with a porous structure is formed using the MOF material as a template; the metal ions and phosphorus in the MOF material form metal phosphides during the calcination process, and the metal phosphides tend to be enriched on the surface of the carbon-based layer, forming the outermost shell of the negative electrode material.
[0038] The preparation method according to a preferred embodiment of the present invention has at least the following beneficial effects:
[0039] (1) The present invention innovatively proposes and realizes the use of phosphorus in MOF materials as a phosphorus source for synthesizing metal phosphides. Therefore, there is no need to add a phosphorus source again in the subsequent preparation process, which not only saves the process but also avoids the uneven distribution problem caused by the additional addition of a phosphorus source; and improves the uniformity of the distribution of the metal phosphide on the surface of the negative electrode material.
[0040] (2) The present invention uses MOF material as a precursor of the carbon-based layer. The MOF material has a large specific surface area, a porous structure and an inherent carbon skeleton. The carbon-based layer generated by carbonization will inherit the advantages of the MOF material and improve the electrochemical performance of the negative electrode material;
[0041] In addition, since the MOF material will shrink to a certain extent during the calcination process, a certain gap will be generated between the metal phosphide and the carbon-based layer in the obtained negative electrode material, that is, a hollow structure, which further increases the specific surface area of the obtained negative electrode material, effectively alleviating the volume change during the charge and discharge process, fully exposing the active sites and shortening the ion diffusion distance.
[0042] (3) The preparation method of the present invention combines the advantages of MOF materials, silicon-based particles and metal phosphides, while avoiding their respective original disadvantages, thereby obtaining a negative electrode material with excellent comprehensive performance.
[0043] (4) The preparation method provided by the present invention is simple to operate, has mild reaction conditions, is environmentally friendly, and is suitable for industrial production.
[0044] In some embodiments of the present invention, in step S1, the silicon-based particles are nano-silicon. In some embodiments of the present invention, in step S1, the particle size of the silicon-based particles is 200-500 nm.
[0045] In some embodiments of the present invention, in step S1, the amount of silicon-based particles added is 1 to 2 g.
[0046] In some embodiments of the present invention, in step S1, the molar ratio of the metal salt to the silicon-based particles is about 1:(3-6).
[0047] In some embodiments of the present invention, in step S1, the metal salt includes at least one of a nickel salt, a cobalt salt, a molybdenum salt and an iron salt.
[0048] In some embodiments of the present invention, in step S1, the anion of the metal salt includes at least one of chloride ion, sulfate ion and nitrate ion.
[0049] In some embodiments of the present invention, in step S1, the phosphorus-containing ligand includes at least one of hydroxyethylidene diphosphonic acid and glyphosate.
[0050] In some embodiments of the present invention, in step S1, the ligand further includes a nitrogen-containing ligand.
[0051] In some preferred embodiments of the present invention, the nitrogen-containing ligand includes at least one of pyrazine, bipyridine (bpy) and o-phenanthroline (Phen).
[0052] In some embodiments of the present invention, in step S1, the molar ratio of the metal salt to the phosphorus-containing ligand is 1:(1-2).
[0053] In some embodiments of the present invention, the molar ratio of the metal salt, the phosphorus-containing ligand and the nitrogen-containing ligand is 1:(1-2):(1-2).
[0054] In some embodiments of the present invention, in step S1, the molar ratio of the metal salt to the ligand is 1:(1-4).
[0055] In some preferred embodiments of the present invention, in step S1, the molar ratio of the metal salt to the ligand is 1:(2-4).
[0056] In some embodiments of the present invention, in step S1, the solvent used in the solvothermal reaction includes at least one of N,N-dimethylformamide (DMF), methanol and ethanol.
[0057] In some embodiments of the present invention, in step S1, in the solvothermal reaction, the ratio of the volume of the solvent to the mass of the silicon-based particles is 2-3 mL:0.1 g.
[0058] In some embodiments of the present invention, in step S1, the temperature of the solvothermal reaction is 100-150°C.
[0059] In some embodiments of the present invention, in step S1, the duration of the solvothermal reaction is 10 to 16 hours.
[0060] In some embodiments of the present invention, in step S1, before the solvothermal reaction, the step further includes dispersing the silicon-based particles, the metal salt and the ligand in the solvent.
[0061] In some embodiments of the present invention, the dispersing comprises first stirring the metal salt, the ligand and the solvent, and then adding the silicon-based particles and performing ultrasound.
[0062] In some embodiments of the present invention, the stirring time is 30 to 60 minutes.
[0063] In some embodiments of the present invention, the power of the ultrasound is 60-90%.
[0064] In some embodiments of the present invention, the 100% power of the ultrasound is 150W.
[0065] In some embodiments of the present invention, the duration of the ultrasound is 30 to 60 minutes.
[0066] In some embodiments of the present invention, step S1 further includes washing and drying the obtained solid after the solid-liquid separation.
[0067] In some embodiments of the present invention, the cleaning comprises washing with water and 30-99.5 wt % ethanol solution in sequence.
[0068] In some embodiments of the present invention, solid-liquid separation is required after the washing.
[0069] In some embodiments of the present invention, in step S1, all solid-liquid separation steps can be performed by centrifugation.
[0070] In some embodiments of the present invention, the rotation speed of the centrifugation method is 8000-10000 rpm.
[0071] In some embodiments of the present invention, the drying temperature is 50-70°C.
[0072] In some preferred embodiments of the present invention, the drying temperature is about 60°C.
[0073] In some embodiments of the present invention, the drying time is 10 to 18 hours.
[0074] In some preferred embodiments of the present invention, the drying time is about 12 hours.
[0075] In some preferred embodiments of the present invention, the drying method is vacuum drying.
[0076] In some embodiments of the present invention, in step S2, the protective atmosphere includes at least one of nitrogen and an inert gas.
[0077] In some embodiments of the present invention, in step S2, the constant temperature of calcination is 450-550°C.
[0078] In some embodiments of the present invention, in step S2, the constant temperature time of calcination is 4 to 6 hours.
[0079] In some embodiments of the present invention, in step S2, the heating rate of the calcination is 2-7°C / min.
[0080] In some embodiments of the present invention, step S2 further includes washing after the calcination.
[0081] In some embodiments of the present invention, the post-calcination washing comprises at least one of a water wash and an ethanol wash.
[0082] According to another aspect of the present invention, a negative electrode is provided, and the preparation raw materials include the negative electrode material or the negative electrode material prepared by the preparation method.
[0083] The negative electrode according to a preferred embodiment of the present invention has at least the following beneficial effects:
[0084] The present invention synthesizes a negative electrode material with a core-shell structure of metal phosphide-coated silicon-carbon by a simple method, introduces highly stable N and C sources, and forms a high-performance composite negative electrode material. The volume expansion of the negative electrode prepared by the material can be effectively suppressed during the charge and discharge process, thereby improving the endurance of the silicon negative electrode for lithium-ion batteries, while having high capacity and high rate performance.
[0085] In some embodiments of the present invention, the method for preparing the negative electrode comprises the following steps:
[0086] D1. After dry mixing the conductive agent and the negative electrode material, dry mixing with the binder;
[0087] D2. The mixture obtained in step D1 and the diluent are mixed and homogenized;
[0088] D3. Apply the slurry obtained in step D2 on the current collector, dry it, and roll it.
[0089] In some embodiments of the present invention, in step D1, the conductive agent includes at least one of acetylene black and graphene.
[0090] In some embodiments of the present invention, in step D1, the binder includes at least one of styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC) and polyvinylidene fluoride (PVDF).
[0091] In some preferred embodiments of the present invention, in step D1, the binder is a mixture of styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC).
[0092] In some embodiments of the present invention, in step D1, the mixing method is dry mixing.
[0093] In some embodiments of the present invention, in the mixture obtained in step D1, the silicon-carbon material accounts for 70-80% by mass; the conductive agent accounts for 10-20%; the binder accounts for 10-20%;
[0094] The binder comprises 5-10% CMC and 5-10% SBR.
[0095] In some embodiments of the present invention, in step D2, the diluent includes water or N,N-dimethyldiamide.
[0096] In some embodiments of the present invention, in some embodiments of the present invention, in step D2, the solid content of the slurry is 40-60 wt%.
[0097] In some embodiments of the present invention, in step D2, the viscosity of the slurry is 4500-6000 cps.
[0098] In some embodiments of the present invention, in step D3, the current collector comprises copper foil.
[0099] According to another aspect of the present invention, a secondary battery is provided, comprising the negative electrode.
[0100] Unless otherwise specified, "about" in the present invention means that the allowable error is between ±2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0101] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0102] Figure 1 This is a schematic diagram of the process of Example 1 of the present invention;
[0103] Figure 2 The cycle performance of the battery obtained by the application example of the present invention;
[0104] Figure 3 The adsorption-desorption isotherm of the negative electrode material obtained in Example 1;
[0105] Figure 4 This is the SEM image of the negative electrode material obtained in Example 1. DETAILED DESCRIPTION
[0106] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0107] If not otherwise specified, the operating temperature in the specific embodiments is about 25°C;
[0108] Metal salts, hydroxyethylidene diphosphonic acid, and pyrazine were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0109] Nano-silicon was purchased from Guangdong Brunp Recycling Technology Co., Ltd., with a particle size ranging from 200 to 500 nm;
[0110] DMF and hydrochloric acid were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0111] Example 1
[0112] This embodiment prepares a negative electrode material, and the specific process is as follows:
[0113] S1. Preparation of precursor:
[0114] S1a. MOF raw material mixing: 0.01 mol cobalt nitrate, 0.01 mol hydroxyethylidene diphosphonic acid (C2H8O7P2, HEDP) and 0.01 mol pyrazine (C4H4N2) were dissolved in 20 mL of N,N-dimethylformamide (DMF) and magnetically stirred for 30 min to completely dissolve the materials;
[0115] S1b. Add 1 g of nano-silicon to the mixture obtained in step S1a, set the ultrasonic power to 90%, and ultrasonically disperse for 30 min;
[0116] S1c. The mixture obtained in step S1b was transferred into a reactor and reacted at 100 ° C for 15 h;
[0117] S1d. The mixture obtained in step S1c was cooled, centrifuged at a speed of 8000 rpm, the solid was washed with distilled water and ethanol solution, and dried at 70 ° C for 10 h to obtain a precursor;
[0118] S2. The precursor obtained in step S1 is heated to 550°C in a tubular furnace under a N2 atmosphere and calcined at a constant temperature of 4 h at a heating rate of 7°C / min. After cooling in the furnace, the obtained product is washed with distilled water until it is neutral, filtered, and the solid is dried at 70°C for 6 h.
[0119] The flow chart of this embodiment is as follows Figure 1 shown.
[0120] Example 2
[0121] This embodiment prepares a negative electrode material, and the specific process is as follows:
[0122] S1. Preparation of precursor:
[0123] S1a. MOF raw material mixing: 0.01 mol cobalt nitrate, 0.02 mol hydroxyethylidene diphosphonic acid (C2H8O7P2, HEDP) and 0.02 mol pyrazine (C4H4N2) were dissolved in 30 mL of N,N-dimethylformamide (DMF) and magnetically stirred for 60 min to completely dissolve the materials;
[0124] S1b. Add 1.5 g of nano-silicon to the mixture obtained in step S1a, set the ultrasonic power to 70%, and ultrasonically disperse for 60 min;
[0125] S1c. The mixture obtained in step S1b was transferred into a reactor and reacted at 150°C for 10h;
[0126] S1d. The mixture obtained in step S1c was cooled and centrifuged at 10000 rpm, the solid was washed several times with distilled water and ethanol solution, and dried at 60 ° C for 12 h to obtain a precursor;
[0127] S2. The precursor obtained in step S1 is heated to 450°C in a tubular furnace under a N2 atmosphere and calcined at a constant temperature for 6 hours at a heating rate of 2°C / min. After cooling in the furnace, the obtained product is washed with distilled water until it is neutral, filtered, and the solid is dried at 70°C for 6 hours.
[0128] Example 3
[0129] This embodiment prepares a negative electrode material, and the specific process is as follows:
[0130] S1. Preparation of precursor:
[0131] S1a. MOF raw material mixing: 0.01 mol nickel chloride, 0.01 mol hydroxyethylidene diphosphonic acid (C2H8O7P2, HEDP) and 0.01 mol pyrazine (C4H4N2) were dissolved in 20 mL of N,N-dimethylformamide (DMF) and magnetically stirred for 30 min to completely dissolve the materials;
[0132] S1b. Add 1 g of nano-silicon to the mixture obtained in step S1a, set the ultrasonic power to 90%, and ultrasonically disperse for 30 min;
[0133] S1c. The mixture obtained in step S1b was transferred into a reactor and reacted at 100 ° C for 15h;
[0134] S1d. The mixture obtained in step S1c was cooled, centrifuged at a speed of 8000 rpm, and the solid was washed several times with distilled water and ethanol solution, and dried at 70 ° C for 10 h to obtain a precursor;
[0135] S2. The precursor obtained in step S1 is heated to 550°C in a tubular furnace under a N2 atmosphere and calcined at a constant temperature of 4 h at a heating rate of 7°C / min. The product is cooled in the furnace and washed with distilled water until it is neutral, filtered, and dried at 70°C for 6 h.
[0136] Example 4
[0137] This embodiment prepares a negative electrode material, and the specific process is as follows:
[0138] S1. Preparation of precursor:
[0139] S1a. MOF raw material mixing: 0.01 mol nickel chloride, 0.02 mol hydroxyethylidene diphosphonic acid (C2H8O7P2, HEDP), and 0.02 mol pyrazine (C4H4N2) were dissolved in 30 mL of N,N-dimethylformamide (DMF) and magnetically stirred for 60 min to completely dissolve the materials;
[0140] S1b. Add 1.5 g of nano-silicon to the mixture obtained in step S1a, set the ultrasonic power to 70%, and ultrasonically disperse for 60 min;
[0141] S1c. The mixture obtained in step S1b was transferred into a reactor and reacted at 150 ° C for 10 h;
[0142] S1d. The mixture obtained in step S1c was cooled, centrifuged at a speed of 10000 rpm, and the solid was washed several times with distilled water and ethanol solution, and dried at 60 ° C for 12 h to obtain a precursor;
[0143] S2. The precursor obtained in step S1 is heated to 450°C in a tubular furnace under a N2 atmosphere and calcined at a constant temperature of 6 h at a heating rate of 2°C / min. The product is cooled in the furnace and washed with distilled water until it is neutral, filtered, and dried at 70°C for 6 h.
[0144] Example 5
[0145] This embodiment prepares a negative electrode material, and the specific process is as follows:
[0146] S1. Preparation of precursor:
[0147] S1a. MOF raw material mixing: 0.01 mol ferrous chloride, 0.01 mol hydroxyethylidene diphosphonic acid (C2H8O7P2, HEDP) and 0.01 mol pyrazine (C4H4N2) were dissolved in 20 mL of N,N-dimethylformamide (DMF) and stirred magnetically for 30 min to completely dissolve the materials;
[0148] S1b. Add 1 g of nano-silicon to the mixture obtained in step S1a, set the ultrasonic power to 90%, and ultrasonically disperse for 30 min;
[0149] S1c. The mixture obtained in step S1b was transferred into a reactor and reacted at 100 ° C for 15 h;
[0150] S1d. The mixture obtained in step S1c was cooled, centrifuged at a speed of 8000 rpm, and the solid was washed several times with distilled water and ethanol solution, and dried at 70 ° C for 10 h to obtain a precursor;
[0151] S2. The precursor obtained in step S1 is heated to 550°C in a tubular furnace under a N2 atmosphere and calcined at a constant temperature for 4 hours at a heating rate of 7°C / min. The product is washed with distilled water until it is neutral, filtered, and the solid is dried at 70°C for 6 hours.
[0152] Example 5
[0153] This embodiment prepares a negative electrode material, and the specific process is as follows:
[0154] S1. Preparation of precursor:
[0155] S1a. MOF raw material mixing: 0.01 mol ferrous chloride, 0.02 mol hydroxyethylidene diphosphonic acid (C2H8O7P2, HEDP) and 0.02 mol pyrazine (C4H4N2) were dissolved in 30 mL of N,N-dimethylformamide (DMF) and magnetically stirred for 60 min to completely dissolve the materials;
[0156] S1b. Add 1.5 g of nano-silicon to the mixture obtained in step S1a, set the ultrasonic power to 70%, and ultrasonically disperse for 60 min;
[0157] S1c. The mixture obtained in step S1b was transferred into a reactor and reacted at 150 ° C for 10 h;
[0158] S1d. The mixture obtained in step S1c was cooled, centrifuged at a speed of 10000 rpm, and the solid was washed several times with distilled water and ethanol solution, and dried at 60 ° C for 12 h to obtain a precursor;
[0159] S2. The precursor obtained in step S1 is heated to 450°C in a tubular furnace under a N2 atmosphere and calcined at a constant temperature of 6 h at a heating rate of 2°C / min. After cooling in the furnace, the product is washed with distilled water until it is neutral, filtered, and the solid is dried at 70°C for 6 h.
[0160] Comparative Example 1
[0161] This comparative example prepares a negative electrode material, which differs from Example 4 in that:
[0162] (1) The ligand in step S1a does not include hydroxyethylidene diphosphonic acid, but only includes 0.02 mol of pyrazine;
[0163] (2) The metal salt in step S1a is ferrous chloride instead of nickel chloride.
[0164] Application Examples
[0165] In this application example, the nano silicon used in Examples 1 to 6 and the obtained negative electrode material are used as negative electrode active materials to prepare negative electrode sheets. The specific method is as follows:
[0166] D1. After dry mixing 15% acetylene black and 75% negative electrode active material (obtained from Examples 1 to 6, respectively, and the nanomaterial used) by weight percentage, 5% CMC and 5% SBR were added and continued to dry mix;
[0167] D2. The mixture obtained in step D1 is dispersed in water to form a slurry having a solid content of 50 wt% and a viscosity of 4500 to 6000 cps;
[0168] D3. The slurry obtained in step D2 is coated on the current collector and then rolled to obtain a coating thickness of 90 to 140 μm (the thickness at different positions fluctuates within the above range) and a compaction density of 1.70 to 1.90 g / cm 3 (Compaction at different locations fluctuates within the above range).
[0169] Test example
[0170] This test example tests the electrochemical cycle performance of the nano-silicon and the obtained negative electrode materials used in Examples 1 to 6. The test conditions are: the test battery is a button battery formed by the negative electrode obtained in the application example and a lithium sheet, the test voltage is 0.02-1.2V, the test current is 4A / g, and the test results are as follows: Figure 2 shown.
[0171] Figure 2The results show that at a high current density of 4A / g, the negative electrode materials obtained in Examples 1 and 3 still have a reversible capacity of 1287.18mAh / g after 800 cycles, and the capacity retention rate is 71.8%. When pure nano-silicon is used as the negative electrode active material, the capacity of the obtained battery decays to about 250mAh / g after 100 cycles. The above results show that compared with nano-silicon, the cycle performance of the negative electrode material obtained in the present invention is significantly improved.
[0172] This example also tests the physical and chemical properties of the negative electrode material obtained in Example 1, specifically testing the specific surface area and microscopic morphology of the negative electrode material.
[0173] Figure 3 This is the adsorption-desorption isotherm of the negative electrode material obtained in Example 1. The testing method is as follows: the powder sample to be tested is placed in a U-shaped sample tube, a mixed gas containing a certain proportion of adsorbate flows through the sample, and the adsorption amount (BET) of the adsorbate molecule (N2) of the tested sample is determined based on the change in gas concentration before and after adsorption.
[0174] Figure 3 The results show that the sample has a typical H3 hysteresis loop, indicating that it is a mesoporous material, and has a high adsorption and desorption capacity when P / P0<0.02, indicating that it has a relatively large microporous structure, that is, the material is a porous material mainly composed of micropores and mesopores. Through fitting, it is found that the specific surface area of the negative electrode material obtained by the present invention is 300-400m 2 / g.
[0175] The negative electrode material obtained by the present invention is spherical, and the main particle size distribution is between 1 and 3 μm. The specific morphology is as follows Figure 4 As shown, the outer layer of each sphere is brighter. According to the thickness contrast, it can be seen that the sphere (negative electrode material) has a core-shell structure, but the outermost shell structure is very thin.
[0176] Characterization shows that the physical and chemical properties of the materials obtained in Examples 1 to 5 are comparable, and all of them have a core-shell structure and a relatively high specific surface area.
[0177] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A negative electrode material, It is characterized in that include: A silicon-based core, a carbon-based layer wrapping the silicon-based core, and a metal phosphide wrapped on the surface of the carbon-based layer; The carbon-based layer has a pore structure; The metal phosphide is cobalt phosphide; There is a gap between the carbon-based layer and the metal phosphide; The negative electrode material is prepared by a preparation method comprising the following steps: S1. Solvent thermal reaction of silicon-based particles, metal salts and ligands followed by solid-liquid separation to obtain silicon-based particles wrapped with MOF; the ligands include phosphorus-containing ligands; S2. calcining the MOF-encapsulated silicon-based particles in a protective atmosphere; The metal salt is a cobalt salt; In step S1, the temperature of the solvent thermal reaction is 100-150°C and the duration is 10-16 hours; In step S2, the calcination is carried out at a constant temperature of 450-550°C and a constant temperature time of 4-6 hours.
2. The negative electrode material according to claim 1, It is characterized in that The particle size of the negative electrode material is 1-3 μm.
3. The negative electrode material according to claim 1, It is characterized in that The specific surface area of the negative electrode material is 300-400 m 2 / g.
4. The negative electrode material according to claim 1, It is characterized in that In step S1, the phosphorus-containing ligand includes at least one of hydroxyethylidene diphosphonic acid and glyphosate.
5. The negative electrode material according to claim 1, It is characterized in that In step S1, the ligand further includes a nitrogen-containing ligand.
6. The negative electrode material according to claim 1, It is characterized in that In step S1, the molar ratio of the metal salt to the phosphorus-containing ligand is 1:(1-2).
7. The negative electrode material according to claim 1, It is characterized in that In step S2, the heating rate of the calcination is 2-7°C / min.
8. A negative electrode, It is characterized in that The preparation raw materials include the negative electrode material according to any one of claims 1 to 7.
9. A secondary battery, It is characterized in that Comprising the negative electrode as claimed in claim 8.
